316 Reduction of musculoskeletal pain among professional musicians by introducing resistance band training at work. (24th April 2018) - Brandt, LPA; Panduro, MB; Nielsen, SR
Abstract : Introduction: Several studies have shown that professional symphony orchestra musicians have a higher prevalence of musculoskeletal complaints (MSC), compared to other work groups. MSC have a great impact on the musicians' workability and life quality, emphasising the importance of finding preventive measures Methods: A cross-sectional study, based on questionnaires before and after an intervention of resistance band training, among 350 musicians and administrative workers from 5 symphony orchestras in Denmark. The participant rated their degree of pain on a VAS scale from 0 to 10 and overall reduction of MSC. The changes from baseline to follow-up for each separate body region were evaluated using a linear mixed model. Result: MSC was most common in shoulders, neck, and lower back. Female musicians had a significantly higher prevalence of MSC than men. Low string group had the lowest prevalence of MSC, while high string, brass-winds and woodwind groups had a relative high prevalence of MSC. Resistance band training showed a positive significant effect with a mean reduction of VAS-scores in shoulders at −0.88 and neck at −0.52. 45% of the participants experienced an overall reduction in musculoskeletal pain. Discussion: In compliance with the purpose, MSC before and after the intervention were assessed, showing a positive effect with regards to MSC in shoulders and neck. Future research should explore how realistic implementing resistance band training is as a steady regime among professional symphony orchestra musicians, likewise assuring a long lasting positive effect.